Pengaruh ROA dan FDR Terhadap Struktur Modal Pada Bank Umum Syariah di Indonesia Tahun 2019-2023 - Ade Azizah; Toto Suharto; Mohammad Iqbal (CIEBER: Contemporary Islamic Economic and Business Review, 2025)
This research aims to investigate the effect of profitability and liquidity on the capital structure of Sharia Commercial Banks (BUS) in Indonesia during the 2019-2023 period. Using samples from 10 BUS, this research analyzes data covering 50 observations to test the proposed hypothesis. The analytical method used is multiple linear regression to determine the relationship between the independent variables profitability and liquidity and the dependent variable capital structure as measured by the Capital Adequacy Ratio (CAR). The research results show that liquidity has a positive and significant influence on capital structure, while profitability has a negative influence on capital structure. These findings indicate that increasing liquidity, as measured through the Financing to Deposit Ratio (FDR), contributes to increasing the Capital Adequacy Ratio (CAR), which is an important indicator of a bank's financial health. This research also emphasizes the importance of effective liquidity management in supporting a healthy capital structure in Sharia Commercial Banks (BUS). Thus, the results of this research contribute to the development of capital structure theory and financial management practices in the Islamic banking industry. It is hoped that this research can become a reference for future researchers and provide insight for bank management in making decisions regarding liquidity and capital structure.